Air quality and health co-benefits of China's national emission trading system. (1st March 2020) - Chang, Shiyan; Yang, Xi; Zheng, Haotian; Wang, Shuxiao; Zhang, Xiliang
Highlights: The Emission Trading System will bring about considerable air quality co-benefits. The PM2.5 concentration is reduced under the Emission Trading System. The reduction of the exposure to PM2.5 causes the nationwide health improvement. The morbidity and mortality are reduced under the Emission Trading System. GDP loss can be partially offset considering the health benefits. Abstract: Quantification of the air quality and health co-benefits of climate policies can provide explicit near-term localized assessment of the benefits of efforts to mitigate climate change. In the study, the air quality and PM2.5 associated health co-benefits of China's national Emission Trading System to achieve the Nationally Determined Contribution is analyzed. The interdisciplinary integrated assessment model framework, named the Regional Emissions Air quality Climate Health Model, is applied. The results showed that substantial air quality improvement and health benefit will be achieved under the national Emission Trading System. But the cost and benefits varies according to the CO2 emission cap set. To peak CO2 emissions by 2025 will bring about more obvious improvement in air quality (ranging from 3% to 12% PM2.5 concentration reduction at provincial level compared with that to peak CO2 emission by 2030), more morbidities avoided from acute exposure and more mortalities avoided from acute exposure and chronic exposure. While the net health benefit to achieve peaking by 2025 is US$ 100 billion less than that to achieve peaking by 2030 due to greater GDP loss in 2030. The net benefit is subjected to the valuation of the health benefits. If a higher Value of a Statistical Life, US$ 1.92 million, is chosen, the net benefits to achieve peak CO2 emissions by 2025 can be equal to that to achieve peak CO2 emissions by 2030.